The Effect of Brand Image, Product Quality, and Product Design on Consumer Decisions When Choosing L'oréal Products in Malang - Ardi Sila Artha; Rafika Cahya Maharani (Journal of Management, Entrepreneurship, and Tourism, 2026)
This study investigates the structural pathways through which brand image, product quality, and product design shape consumer purchasing decisions within the competitive cosmetics industry in Malang, Indonesia. Utilizing an empirical quantitative approach with an explanatory survey research design, primary data were gathered via structured digital questionnaires from a purposive sample of 100 qualified L'Oréal consumers. Data analysis was executed using Variance Based Structural Equation Modeling via Partial Least Squares to evaluate both measurement parameters and structural linkages. The outer model evaluation substantiated robust psychometric properties, satisfying all convergent validity, discriminant validity, and internal consistency reliability thresholds. The inner model assessment revealed that the hypothesized framework explains 72.4% of the variance in consumer choices. The empirical findings demonstrate that product design emerges as the primary visual driver of consumer selection, followed sequentially by product quality as a functional justification and brand image as a risk mitigation anchor. These outcomes indicate that modern cosmetic selection is heavily guided by experiential aesthetic traits and immediate sensory gratification, which significantly condense traditional multi attribute evaluation steps.